2017
DOI: 10.1007/s11864-017-0496-7
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Classification and Treatment of Ependymomas

Abstract: Ependymomas are a subgroup of ependymal glia-derived neoplasms that affect children as well as adults. Arising within any CNS compartment, symptoms at presentation can range from acute onset due to increased intracranial pressure to insidious myelopathy. The overall survival (OS) outcomes in adult patients across the subgroups is heterogeneous with subependymoma having an excellent prognosis often even in the absence of any treatment, whereas supratentorial ependymomas tend to be higher grade in nature and may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 44 publications
1
14
0
1
Order By: Relevance
“…PF-SE carries low pathogenicity and, in fact, is often not discovered until postmortem examination [ 64 , 65 ]. GTR is generally thought to be curative, though recurrences can occur [ 62 , 66 ]. Radiotherapy may be used in cases of STR, but is typically reserved as salvage therapy if progression occurs.…”
Section: Subependymoma (Se)mentioning
confidence: 99%
“…PF-SE carries low pathogenicity and, in fact, is often not discovered until postmortem examination [ 64 , 65 ]. GTR is generally thought to be curative, though recurrences can occur [ 62 , 66 ]. Radiotherapy may be used in cases of STR, but is typically reserved as salvage therapy if progression occurs.…”
Section: Subependymoma (Se)mentioning
confidence: 99%
“…This result underlines the fact that miRNA are pluripotent molecules and their role in tumorigenesis in given tumor type needs to be elucidated by more studies especially in tumors of genetically heterogeneous nature. Tumor grading in ependymoma reveals high interindividual variability (19). This fact calls for new markers which would make distinguishing between low-grade and high-grade lesion more convenient.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been reported that the level of resection does not significantly affect the outcome within the STEPN- RELA -positive subgroup in a retrospective analysis for patient samples collected over a long period of time over 20 years [ 25 ]. ST-EPN- YAP1 subgroup is associated with favorable clinical outcome [ 13 , 15 ]. Clinical trials with de-escalating therapy could be recommended for this subgroup.…”
Section: Treatment Decision In Molecular Eramentioning
confidence: 99%